Design and analysis of optimised class E power amplifier using shunt capacitance in the output structure. Issue 5 (4th May 2017) - Hayati, Mohsen; Roshani, Sobhan; Zirak, Ali Reza
ABSTRACT: In this paper, a class E power amplifier (PA) with operating frequency of 1 MHz is presented. MOSFET non-linear drain-to-source parasitic capacitance, linear external capacitance at drain-to-source port and linear shunt capacitance in the output structure are considered in design theory. One degree of freedom is added to the design of class E PA, by assuming the shunt capacitance in the output structure in the analysis. With this added design degree of freedom it is possible to achieve desired values for several parameters, such as output voltage, load resistance and operating frequency, while both zero voltage and zero derivative switching (ZVS and ZDS) conditions are satisfied. In the conventional class E PA, high value of peak switch voltage results in limitations for the design of amplifier, while in the presented structure desired specifications could be achieved with the safe margin of peak switch voltage. The results show that higher operating frequency and output voltage can also be achieved, compared to the conventional structure. PSpice software is used in order to simulate the designed circuit. The presented class E PA is designed, fabricated and measured. The measured results are in good agreement with simulation and theory results.